Penggunaan Media Gambar dalam Pembelajaran Kosa Kata di Madrasah Diniyah Takmiliyah Ulul Albab Batan Blaru Badas Kediri - Luthfi, Ibnu Mas'ud (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2023)
Based on the results of the learning evaluation of class II students at Madrasah Diniyah Takmiliyah Ulul Albab Batan Blaru Badas Kediri for Arabic language subjects, more than 50% of their scores are still below the Minimum Completeness Criteria (KKM). One of the reasons is that they do not understand Arabic texts, and one way to overcome this is to increase vocabulary mastery. The more vocabulary you know, the easier it will be to deal with Arabic texts. The research was conducted at Madrasah Diniyah Takmiliyah Ulul Albab Batan Blaru Badas Kediri with the aim of determining the problems of vocabulary learning and its causal factors and describing the steps of vocabulary learning with image media. The method used by the researcher was a qualitative method with a descriptive approach. Meanwhile, the approach used by the researcher is in the form of a descriptive approach because the researcher will describe the use of media images in learning vocabulary at Madrasah Diniyah Takmiliyah Ulul Albab Batan Blaru Badas Kediri. The goal of learning vocabulary was not achieved properly at Madrasah Diniyah Takmiliyah Ulul Albab Batan Blaru Badas Kediri because previous learning was carried out online which was less specific and there were several students who graduated from kindergarten who had never learned Arabic. In addition, students' interest and motivation in learning is still low and teachers have not used instructional media other than teacher books and student books.